Prevalence of Modern Teaching Method among Senior High School Students - Martin, Matronillo; Laciste, Gilbert; Concepcion, Kristine (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
The main purpose of this study is to determine the effectiveness of the modern teaching method to teaching learning process. The descriptive-quantitative method was employed using a questionnaire as data gathering instrument. Frequencies, percentages and weighted mean were used to treat the data. The target population of the study was 286 of the senior high school students of the University of La Salette, Inc. – Santiago City during the school year 2018-2019. The study showed that modern teaching method has a positive impact on the learning of the students. It gives a lot of benefits that characterize a life-long learning. Also, through the modern teaching a method, students will be able to learn some values that will lead them to success. It also revealed that among the four-teaching method, brainstorming is the most effective for the students to learn. Based on the findings and conclusions of the study, it was recommended that teachers need to continually develop a method that will let their students easily to learn and in order to cope up with the needs of the students. They should always reflect on their own methods to improve the teaching learning process.  Also, in choosing an appropriate teaching method, teachers should consider his or her subject matter and students. It is not necessary that brainstorming is always effective in teaching learning process thus, when a teacher employ a teaching method he/she needs to exert an effort to fully experience the effectiveness of the teaching method. It also recommended that future researchers must use an experimentation design to determine the effectiveness of the different teaching method.